Acetogeninas isoladas de sementes de Annona coriacea do cerrado mato-grossense e sua atividade larvicida sobre Aedes aegypti (LINNAEUS) - Alves, Thayana da Conceição (2012)
Dengue is a major public health problem worldwide, with increasing rates of cases each year in the Brazilian states, especially in the Midwest. Studies in search of new substances from plant with insecticidal activity have been extensively realized in recent years, such as the use of plant extracts as an alternative method to control the mosquito vector, Aedes aegypti. The Annonaceae family has featured the Brazilian Cerrado for possessing a class of substances that exhibit various biological activities such as cytotoxic, fungicidal among others and some species of this family showed insecticidal activity against larvae and adults of A. aegypti. This work describe the biomonitored study of phytochemical seeds of Annona coriacea from the Cerrado of Mato Grosso through testing larvicidal activity against the A. aegypti. The biologicals testing of extracts and fractions showed that the species is as promising source of compounds insecticides, because several samples have shown high larvicide potential with superior results to those of other species of the Annona genus. The results of the larvicidal activity of extracts and fractions showed a direct increase in the biological potential with chromatographic purification of the samples. The chemical study of A. coriacea hexane and methanol active extracts allowed to the isolation/elucidation of three substances, including two novel: the mono-THF acetogenins α,α-dihydroxylated, named coriapentocina A and B, and a bis-THF α,α-dihydroxylated acetogenin already described in literature and known as bullacina. Among these, the bullacina acetogenin showed high larvicide potential against A. aegypti (100% mortality) a biological activity reported for the first time for this acetogenin. Already coriapentocina A showed significant larvicidal activity (75% mortalidade). The activities found for bullacina and coriapentocina A corroborate to the biological activity described for acetogenins which are associated with the presence of bis-THF and mono-THF group.